The The Correlation Between Nutritional Status And Urine Glucose With Estimated Fetal Weight In Trimester III Pregnant Women At Prima Husada Hospital - Nur Masruroh; Andreas Putro Ragil Santoso (Universitas Nahdlatul Ulama Surabaya, 2021)
The nutritional status of a pregnant woman can be seen from several things, including the Body Mass Index and the diameter of the upper arm circumference. Urine glucose describes the state of glucose in urine. The well-being of a baby in the womb can be measured through the estimated fetal weight according to the gestational age. This study aims to determine the relationship between nutritional status and urine glucose on the estimated fetal weight. Using a cross sectional research method with a sample of 30 respondents taken at the Prima Husada Hospital Sidoarjo during May-July 2020. The results of the analysis of body mass index and estimated fetal weight obtained p value = 0.337 (> 0.05), on the upper arm circumference and estimates fetal weight obtained p value = 0.03 (<0.05) and in urine glucose and fetal weight estimates obtained p value = 0.19 (> 0.05). In conclusion, there is no relationship between body mass index and estimated fetal weight. There is a relationship between the circumference of the upper arm and the estimated fetal weight. And there is no relationship between urine glucose and estimated fetal weight. Women must prepare physically from before pregnancy to optimize future baby growth. Midwives must also regularly provide health education to improve women's health status